STUDIES ON ALTERNARIA BLIGHT OF CARNATION - A. P. S. GILL, J. S. DHlMAN, J. S. ARORA AND (Indian Phytopathology, 2002)
Foliar blight of carnation incited by Alternaria alternata is a serious problem in Northern India. The artificial inoculation of carnation (cv. Scania) twigs with mycelial-spore suspension (c. 10 x 103 m!") resulted in symptom expression after an incubation period of 6 days. The leaves of the basal profile contracted maximum disease. The distal parts of leaves contracted significantly more disease than the promixal ones. The disease tended to decrease as the planting date was delayed. The cultivar Exquisite was found to contract minimum disease.